FSMP-10. CYSTEINE INDUCES CYTOTOXICITY IN GLIOBLASTOMA THROUGH MITOCHONDRIAL HYDROGEN PEROXIDE PRODUCTION. (25th March 2021) - Noch, Evan; Palma, Laura; Yim, Isaiah; Binder, Bhavneet; Benedetti, Elisa; Krumsiek, Jan; Elemento, Olivier; Cantley, Lewis
Abstract: Glioblastoma (GBM) is a poorly treatable disease with high mortality. Tumor metabolism in GBM is a critical mechanism responsible for growth because of upregulation of glucose, amino acid, and fatty acid utilization. However, little is known about the specific metabolic alterations in GBM that are targetable with FDA-approved compounds. To investigate metabolic signatures unique to GBM, we interrogated the TCGA and a cancer metabolite database for alterations in glucose and amino acid signatures in GBM relative to other human cancers and relative to low-grade glioma. From these analyses, we found that GBM exhibits the highest levels of cysteine and methionine pathway gene expression of 32 human cancers and that GBM exhibits high levels of cysteine metabolites compared to low-grade gliomas. To study the role of cysteine in GBM pathogenesis, we treated patient-derived GBM cells with FDA-approved cyst(e)ine-promoting compounds in vitro, including N-acetylcysteine (NAC) and the cephalosporin antibiotic, Ceftriaxone (CTX), which induces cystine import through system Xc transporter upregulation. Cysteine-promoting compounds, including NAC and CTX, inhibit growth of GBM cells, which is exacerbated by glucose deprivation. This growth inhibition is associated with reduced mitochondrial metabolism, manifest by reduction in ATP, NADPH/NADP+ ratio, mitochondrial membrane potential, and oxygen consumption rate. Mechanistic experiments revealed that cysteine compounds induce a rapid increase in the rate of H2 O2 production in isolated GBM mitochondria, an effect blocked by the H2 O2 scavenger, catalase. Such findings are consistent with reductive stress, a ROS-producing process whereby excess mitochondrial reducing equivalents prevent electron transfer to oxidized electron acceptors, inducing O2 reduction to H2 O2 . We show that cysteine-promoting compounds reduce cell growth and induce rapid mitochondrial toxicity in GBM, which may be due to reductive stress. This pathway is targetable with FDA-approved cysteine-promoting compounds and could synergize with glucose-lowering treatments, including the ketogenic diet, for GBM.